2019
DOI: 10.33772/jleet.v4i1.6677
|View full text |Cite
|
Sign up to set email alerts
|

Analysis On The Relationship Of Extrovert-Introvert Personality And Students’ Speaking Performance In English Study Program Of Halu Oleo University

Abstract: Speaking is one of the productive skills in English competence which can help us to interact with other people. However, in a class, not all the students can make equal improvement in speaking skill even though they get the same treatment from the teacher. It happens because there are many factors that influence students’ speaking performance. One of the factors is affective factor that can be from students’ personality. In this category, personality can be classified into two types, they are extrovert and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…Writing skills did not correlate strongly with either of the personality traits. Samand, Sailan, & Lio (2019) found that there is no significant correlation between extrovert personality and speaking performance and neither is introvert personality. Then, other result shows that introvert learners have better achievement in speaking than extrovert learners.…”
Section: Introductionmentioning
confidence: 82%
“…Writing skills did not correlate strongly with either of the personality traits. Samand, Sailan, & Lio (2019) found that there is no significant correlation between extrovert personality and speaking performance and neither is introvert personality. Then, other result shows that introvert learners have better achievement in speaking than extrovert learners.…”
Section: Introductionmentioning
confidence: 82%
“…In line with this finding, Samand et al (2019) also did the study regarding to the relationship between extrovert-introvert personality and students' speaking performance in English study program of Halu Oleo University. The findings of this study indicate that both of extrovert-introvert personality was not correlated significantly with students' speaking achievement.…”
Section: The Inter-correlation Among Extrovert-introvert Personalitymentioning
confidence: 62%
“…Studies on the relationship between personality traits (extrovert and introvert) with oral performance in the EFL context have been well documented, but there are only a few studies have been conducted to find what differences are truly existed between extrovert and introvert personality regarding to their motivational orientations and speaking achievement, and how extrovert and introvert personality are inter-correlated with EFL motivational orientations and speaking achievement. To mention a few, more recent study conducted by Samand et al (2019), which examined the relationship between extrovert-introvert students' personality and their speaking performance, shows that the insignificance correlation between those variables is caused by another factor, namely motivation. However, the study did not provide the empirical evidence of the correlation between motivation and speaking performance.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between personality type and academic achievement is partly influenced by behavior in the classroom [9]. Besides, the research seems to break the theory and previous research that extroverts' students are better than introvert students [10]. Each of the students should have the confidence to make them more comfortable.…”
Section: Related Review Of Literaturementioning
confidence: 73%